If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying E * -3x = 7.1 Reorder the terms for easier multiplication: -3E * x = 7.1 Multiply E * x -3xE = 7.1 Solving -3xE = 7.1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-3E'. x = -2.366666667E-1 Simplifying x = -2.366666667E-1
| 3t-4=4t+16 | | 3x+31=12x-559 | | 17y=3x-19 | | (9+9)=(8-8) | | 10x-63=11 | | 8x^2-9x+k=0 | | 7x-2x-3x+2.73=4.49 | | 3x-5=-41 | | 9p-7= | | z^2+56x-1920=0 | | 7x+12y=12 | | z/-4=11-5 | | 0.7x+0.5=0.9x-1.1 | | 5x-6y=19fory | | 6(3+4x)-8=202 | | 4z/10-1=-8 | | 28-4*X=8 | | 3(4-2n)=2(7-n) | | 0.5/6=120/x | | 5x=12+2y | | 5/x=6/684 | | 3x+5x=150 | | 9-(2y-8)=6-3y | | 10m-26=4 | | -16(0)+128(0)+1680= | | 2x^3-3x=120 | | 2(n+3)=6(n-4) | | 2lm(3x)=8 | | 0=2400/x^2 | | x^2+-12x+36=0 | | 2(x+3)=6(n-4) | | -16t+128t+1680=0 |